The demand for Swiss banknotes: Some new evidence - Katrin Assenmacher-Wesche; Franz Seitz; Jörn Tenhofen (Swiss Journal of Economics and Statistics, 2019)
Knowing the part of currency in circulation that is used for transactions is important information for a central bank. For several countries, the share of banknotes that is hoarded or circulates abroad is sizeable, which may be particularly relevant for large-denomination banknotes. We analyze the demand for Swiss banknotes over a period starting in 1950 to 2017 and use different methods to derive the evolution of the amount that is hoarded. Our findings indicate a sizeable amount of hoarding, in particular for large denominations. The hoarding shares increased around the break-up of the Bretton Woods system, were comparatively low in the mid-1990s, and have increased significantly since the turn of the millennium and the recent financial and economic crises.
Keywords: E41; E52; E58; 330; Currency in circulation; Cash Demand for banknotes; Hoarding of banknotes; Banknotes held by non-residents